Interferometric characterization of an XY piezoeletric nanopositioner: Linearity9 Hysteresis and frequency response - Martinez, Guilherme Alves [UNESP]; Pereira, Fernando Da Cruz; Galeti, Jose Henrique; Higuti, Ricardo Tokio [UNESP]; Nelli Silva, Emilio Carlos; Kitano, Claudio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Piezoelectric motors have been considered successors of electromagnetic motors in areas such as robot joints, high precision machines, micro robots, and MEMS (Micro-Electro-Mechanical Systems). The main interest in this work is the investigation of an XY flextensional positioner adapted for future applications as a rotary piezoelectric motor. To perform this task, the mechanical deformation analysis of the actuator structure was evaluated using finite element software. The results obtained with these simulations were validated using an optical phase detection technique using laser interferometry. Information regarding the linearity between applied voltage and generated displacement, hysteresis, frequency response of displacement and mechanical resonances of the actuator were measured between 0 and 3500 Hz. Simulation and experimental results have brought to light many technical issues that will lead to further investigations, helping the improvement the system in future works.
Keywords: Inteferometry; Metrology; Piezoelectric transducer; Vibration measurement